A shared language regarding sedation and delirium in critically ill patients. Issue 4 (6th May 2015) - Svenningsen, Helle
ABSTRACT Background Patients in intensive care units who develop delirium, experience longer stay in intensive care as well as increased morbidity and mortality. A questionnaire in 2009 showed that there was no consensus in Denmark regarding the tools to be used to assess sedation or delirium, the patient groups they should be used in, or the frequency of assessment. Aims The aims of this survey were to describe clinical practice regarding the assessment of sedation and delirium in intensive care patients and to compare the results with those obtained in 2009. Method A questionnaire was sent via e‐mail to all intensive care units in Denmark caring for ventilated adult patients. An intensive care nurse with daily patient contact was asked to answer questions about the unit's practice regarding the tools used to assess sedation and delirium in adult patients. Results In all, 98% of the intensive care units responded. Richmond Agitation‐Sedation Scale was the most used tool for sedation assessment, and Confusion Assessment Method for the Intensive Care Unit was used only for delirium assessment. Conclusion A shared language for sedation and delirium assessment was identified as essential in supporting care delivery. Relevance to clinical practice A systematic use of a shared language according to sedation and delirium in intensive care units can minimize mistakes in transfer of patients and minimize the risk of doubly traumatising patients.